2006
DOI: 10.1097/01.ccm.0000239195.06781.8c
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal edema decreases intestinal contractile activity via decreased myosin light chain phosphorylation

Abstract: We conclude that edema decreases myosin light chain phosphorylation, leading to decreased intestinal contractile activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 24 publications
(29 reference statements)
3
62
0
Order By: Relevance
“…These data suggest that MLC phosphatase activity is increased. These data agree with our findings in the in vivo intestinal edema model in which intestinal smooth muscle MLC and MYPT1 phosphorylation is decreased (7,14). Previous studies have indicated that PAK is responsive to mechanical signals and can regulate MLC phosphatase activity (22,27,39,40).…”
Section: Effect Of Mechanical Stretching On Mlc Phosphorylation-supporting
confidence: 83%
See 3 more Smart Citations
“…These data suggest that MLC phosphatase activity is increased. These data agree with our findings in the in vivo intestinal edema model in which intestinal smooth muscle MLC and MYPT1 phosphorylation is decreased (7,14). Previous studies have indicated that PAK is responsive to mechanical signals and can regulate MLC phosphatase activity (22,27,39,40).…”
Section: Effect Of Mechanical Stretching On Mlc Phosphorylation-supporting
confidence: 83%
“…Intestinal edema was induced in male Sprague-Dawley rats weighing between 250 and 350 g as described previously (14). Briefly, intestinal edema was induced by a combination of mesenteric venous hypertension and fluid administration (80 ml/kg, 0.9% NaCl).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting study, Uray et al [113] found that the combination of fluid resuscitation and venous hypertension (mimicking IAH) resulted in the highest gut wet-to-dry ratio and gut oedema decreased myosin light chain phosphorylation leading to decreased intestinal contractility. The decrease in contractility may explain why IAH is associated with frequent failure to establish successful enteral nutrition in critically ill patients.…”
Section: Intestinal Oedema Formation In Critically Ill Patients and Imentioning
confidence: 99%